1969
DOI: 10.2466/pr0.1969.25.1.149
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control and Self-Reported Depression among College Students

Abstract: The Internal-External Control, Guilford Depression, and Marlowe-Crowne Social Desirability Scales were administered to 69 university undergraduates to test the hypothesis that depression is associated with belief in external control. The results supported the hypothesis. Implications of the results for notions which link I-E to maladjustment in a U-shaped fashion and for some psychodynamic notions regarding correlates of depression were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
34
1
2

Year Published

1972
1972
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 2 publications
8
34
1
2
Order By: Relevance
“…Recently, Naditch, Gargan, and Michael (1975) found that depressive patients had a more external locus of control than their control subjects. This replicates Abramowitz (1969) and suggests that there is a reliable relationship between mood and locus of control, at least when comparing extreme sadness to normal mood states.…”
supporting
confidence: 76%
“…Recently, Naditch, Gargan, and Michael (1975) found that depressive patients had a more external locus of control than their control subjects. This replicates Abramowitz (1969) and suggests that there is a reliable relationship between mood and locus of control, at least when comparing extreme sadness to normal mood states.…”
supporting
confidence: 76%
“…However, the argument seems implausible for a number of reasons. First, it is known generally that depressed individuals exhibit motivational deficits that interfere with any kind of treatment (Beck, 1967). I n order to maintain S motivation and compliance over the 30-day duration, it was necessary for the therapist to provide all Ss with maximal levels of empathy, warmth, and genuine interest.…”
Section: Reinforcement Expectancymentioning
confidence: 99%
“…The higher the scale score, the more the individual is characterized by an external locus of control. External locus of control has been associated with depression (Abramowitz, 1969), schizophrenia (Harrow & Ferrante, 1969), neuroticism (Nowicki, 1972), and debilitating anxiety (Kendall, Finch, 8c Mahoney, 1976).…”
Section: Instrumentsmentioning
confidence: 99%